Pozitivni učinki telovadbe na sedečem delovnem mestu - Ocvirk, Tjaša (Šport (Ljubljana), 2017)
People have adjusted to technological changes and accepted sedentary way of life. This can have many negative effects to our health, which we can minimalize with regular physical activity. The purpose of article is to present issues of modern workplace and define positive effects of workplace exercises. It was discovered that positive effects of exercise include improvement in mental and physical health. Exercise decreased pain in musculoskeletal structures, mostly in lumbar spine, shoulders and neck. Many of volunteers who did workplace exercise also increased physical activity in their free time, thus there are finding of many pupils improving their body composition. Studies also show decreased percentage of fat and cholesterol, many report about lost kilograms and inches around waist. Consequently to weight drop has risk for type 2 diabetes also decreased. In addition to physical health benefits, studies show improvement in productivity, well-being and lower work absenteeism.
Keywords: corporate fitness; delovno mesto; gibalna dejavnost; health; sedeči način življenja; sedentary way of life; sport; šport; telovadba; zdravje